The analysis of truncated vocatives in Taviano (Salentino) Italian - Michael Kenstowicz (Universitat Autònoma de Barcelona, 2019)
This paper documents and discusses various descriptive generalizations and alternative analyses of the vocative truncation found in the Southern Italian dialect of Taviano that is illustrated by such formations as Filoména > Filomé. We show that the upper limit on the size of the truncate is not restricted by foot binarity nor by internally layered feet: Addoloráta > Addolorá. The lower limit of the truncate may extend to a single CV syllable in violation of foot binarity: Césare > Cé. But truncation to just the stressed vowel is rejected: Élena > *É. We situate the analysis of the vocative truncation within the overall grammar of Salentino and show that while some properties such as the loss of coda consonants can be attributed to rankings imposed by the surrounding grammar, others are peculiar to this construction. The analysis of stress in loanword adaptation figures prominently in our discussion. The final sections examine some of the morphological and syntactic properties of the Taviano vocative.